Social perception of morbidity in facial nerve paralysis. Issue 8 (26th May 2016) - Li, Matthew Ka Ki; Niles, Navin; Gore, Sinclair; Ebrahimi, Ardalan; McGuinness, John; Clark, Jonathan Robert
ABSTRACT: Background: There are many patient‐based and clinician‐based scales measuring the severity of facial nerve paralysis and the impact on quality of life, however, the social perception of facial palsy has received little attention. The purpose of this pilot study was to measure the consequences of facial paralysis on selected domains of social perception and compare the social impact of paralysis of the different components. Method: Four patients with typical facial palsies (global, marginal mandibular, zygomatic/buccal, and frontal) and 1 control were photographed. These images were each shown to 100 participants who subsequently rated variables of normality, perceived distress, trustworthiness, intelligence, interaction, symmetry, and disability. Statistical analysis was performed to compare the results among each palsy. Results: Paralyzed faces were considered less normal compared to the control on a scale of 0 to 10 (mean, 8.6; 95% confidence interval [CI] = 8.30–8.86) with global paralysis (mean, 3.4; 95% CI = 3.08–3.80) rated as the most disfiguring, followed by the zygomatic/buccal (mean, 6.0; 95% CI = 5.68–6.37), marginal (mean, 6.5; 95% CI = 6.08–6.86), and then temporal palsies (mean, 6.9; 95% CI = 6.57–7.21). Similar trends were seen when analyzing these palsies for perceived distress, intelligence, and trustworthiness, using a random effects regression model. Conclusion: Our sample suggests that society views paralyzed faces as less normal, less trustworthy, and more distressed. Different components of facial paralysis are worse than others and surgical correction may need to be prioritized in an evidence‐based manner with social morbidity in mind. © 2016 Wiley Periodicals, Inc. Head Neck 38:1158–1163, 2016